The Non-Structural NS1 Protein Unique to Respiratory Syncytial Virus: A Two-State Folding Monomer in Quasi-Equilibrium with a Stable Spherical Oligome - Pretel, Miguel Esteban (2013)
Human respiratory syncytial virus (hRSV) is a major infectious agent that cause pediatric respiratory disease worldwide. Considered one of the main virulence factors of hRSV, NS1 is known to suppress type I interferon response and signaling, thus favoring immune evasion. This, together with the fact that NS1 is unique to hRSV among paramyxoviruses, and that has no homology within databases, prompted us to investigate its conformational stability, equilibria and folding. Temperature cooperatively induces conformational changes leading to soluble spherical oligomers (NS1SOs) with amyloid-like or repetitive ß-sheet structures. The onset of the thermal transition is 45°C, and the oligomerization rate is increased by 25-fold from 40 to 46°C. Conformational stability analyzed by chemical perturbation of the NS1 monomer shows a two-state, highly reversible and cooperative unfolding, with a denaturant midpoint of 3.8 M, and a free energy change of 9.6±0.9 kcal⋅mol(-1). However, two transitions were observed in the chemical perturbation of NS1SOs: the first, from 2.0 to 3.0 M of denaturant, corresponds to a conformational transition and dissociation of the oligomers to the native monomer, indicating a substantial energy barrier. The second transition (2.0 to 3.5 M denaturant) corresponds to full unfolding of the native NS1 monomer. In addition, different cosolvent perturbations converged on the formation of ß-sheet enriched soluble oligomeric species, with secondary structure resembling those obtained after mild temperature treatment. Thus, a unique protein without homologs, structure or mechanistic information may switch between monomers and oligomers in conditions compatible with the cellular environment and be potentially modulated by crowding or compartmentalization. NS1 may act as a reservoir for increased levels and impact on protein turnover.